Diagnóstico integral ambiental de la ciudad de requena río Ucayali - región Loreto-2022 - Alvarado Chota, Miluska del Pilar (2023)
This work was carried out in the city of Requena, district of the same name, located in the Ucayali river basin, Loreto region, during the year 2022. Descriptive statistics were used, for the presentation of results based on tables and graphs. The objective was to carry out the integral environmental diagnosis together with the environmental perception of the inhabitants, to establish bases towards an appropriate environmental management. The results indicate that this population is aware that there are environmental problems in this city, such as poor solid waste management, noise and gas pollution, accumulation of sewage in the city due to poor drainage, and the need to improve water and drainage services, pollution of the river by fuels, fuels and solid waste, improper use of sand quarries and land fill. Among the most conclusive social factors, for the perception of environmental problems, they refer that this sometimes causes a bad image for the city, in addition to the current population growth, caused changes in the city that were not seen before. They argue that their authorities do not reflect a positive work in favor of solving these problems and do not maintain cordial relations with the population, in addition to the fact that they consider that these problems will not be solved in the near future. They admit that there is environmental contamination (90%) and that the installation of service companies increased environmental problems (75%). They say that sometimes their health is affected by these problems (40%) and they carry out their treatments locally (70%). The lands are devalued those that are located in riverside or floodable areas; they describe that these problems rarely affect their daily life (70%); economic activities are not affected (90%), as is their working life. They are aware that there are environmental problems that must be solved, the population together with their authorities.